Perbedaan Berkumur Larutan Kulit Manggis Dengan Anggur Merah Terhadap Pembentukan Plak Pada Siswa SMPN I Karang Intan Kabupaten Banjar Kalimantan Selatan - metty amperawati; naning K utami (Jurnal Skala Kesehatan, 2019)
Plaque is a major factor in dental caries, gum inflammation and periodontal disease. Dental plaque contains microorganisms composed of 70% bacterial components and 30% consists of inorganic components such as calcium, phosphorus, fluoride and organic components such as carbohydrates, proteins and fats. Mangosteen skin has a therapeutic effect, which can be used to control plaque, gingivitis, halitosis, and prevent tooth decay Grape fruit (Vitis vinifera) has a variety of properties, including preventing caries by inhibiting plaque formation. The purpose of the research is to find out the difference in gargling of mangosteen peel solution with red wine against plaque formation in students of Karang Intan 1 Public High School, Banjar Regency, South Kalimantan. This research is a quasi experiment using the Mann-Whitney test. Research results Mangosteen skin solution and red wine can inhibit plaque formation better than rinsing with plain water. Conclusion there is no difference rinse solution mangosteen rind with red wine on plaque formation. Suggestions For the community, especially school students, they should get used to brushing their teeth, at least gargling after eating, including eating while at school, getting used to eating fruit that is beneficial for dental health. Keywords : Gargling, Mangosteen Skin Solution, red wine solution, plaque